Journal of Human Sport and Exercise - 2019 - Summer Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc5.39
|View full text |Cite
|
Sign up to set email alerts
|

The mediating roles of green brand image and attitude of green branding in the relationship between attachment of green branding and excessive product packaging in Thai sports manufacturing firms

Abstract: The purpose of the study is to narrow down the identified research gap by testing the impact of excessive packaging on green brand attachment empirically. Moreover, the study has analysed the role of green brand image and green brand attitude as mediators in the specified relation. It is expected that the damages caused to brand images by the excessive packaging are revealed by the research findings. This can support the enterprises in the development of strategy for green product packaging from the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A recent study explored that green packaging design appears to be a powerful determinant of green trust, which increases green brand engagement [113]. Another study revealed that the green brand image and green brand behaviour have a favourable impact on green brand engagement [114]. The key contribution of the current study relates to the mediating role of green brand image on the green packaging and branding-green purchase intention relationship.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A recent study explored that green packaging design appears to be a powerful determinant of green trust, which increases green brand engagement [113]. Another study revealed that the green brand image and green brand behaviour have a favourable impact on green brand engagement [114]. The key contribution of the current study relates to the mediating role of green brand image on the green packaging and branding-green purchase intention relationship.…”
Section: Discussionmentioning
confidence: 73%
“…The key contribution of the current study relates to the mediating role of green brand image on the green packaging and branding-green purchase intention relationship. In other words, we can say that green brand image successfully allows firms to increase green purchases by employing green packaging and branding and should avoid excessive packaging of the product as excessive packaging of the product harms green brand image and the green brand attitude of consumers [114,115].…”
Section: Discussionmentioning
confidence: 99%
“…Green brand image is a set of perceptions related to the environment, promises, and obligations (Li et al, 2019), where a customer's cognition of a business idea is created. This cognition ultimately strengthens the customer's connectedness to the brand (Chen et al, 2017;Kerdpitak & Mekkham, 2019). To generate positive image perceptions, brand interaction with customers is needed, where communication has an important interactive contribution.…”
Section: The Effect Of Green Brand Image On Attachmentmentioning
confidence: 99%
“…Green companies may utilize consumer associations to connect their products with feelings in order to elicit a favorable reaction from target consumers once they use a particular brand. Excessive product packaging has been linked in the past to customer brand attitudes and awareness of green brands, which in turn have a favorable association with green brand attachment (Kerdpitak, 2019;Chen, 2017). Previous studies suggest that the primary factor for determining the image of a green brand might be the green brand packaging.…”
Section: Green Brand Packaging and Green Brand Associationsmentioning
confidence: 99%